Assessment of pain severity among metastasized cancer patients in oncology clinic and oncology ward, Hospital Universiti Sains Malaysia - Eleanor Usun, Uben (Universiti Sains Malaysia, 2009)
Cancer pain is the most feared and burdensome symptom. Previous studies have shown that despite the advances of modern treatment modalities for cancer pain, cancer patients by large at a later stage still experienced severe cancer pain. Nurses need to understand these pain experiences by patients to give them the best of care. Therefore, the purposes of this study are (1) to determine the pain severity among metastasized cancer patients; and (2) to determine if there is any difference of the pain severity in relation to age, gender, marital status and occupation. The Multidimensional Model of Cancer Pain (McGuire, 1992) was used to guide this cross sectional, descriptive study which was conducted in the Oncology wards and clinic in HUSM Kelantan. The translated version of Brief Pain Inventory was used to collect the info~mation from the total of 65 female and male cancer patients, with age ranging from 18 to 73 years (50.45 mean age). There was 33 cancer patients at stage Ill and 32 at stage IV and nearly half (47.7%) reported they were given analgesics. By using the Chi square test, the research findings show that 36% female patients reported significant pain than 18.5% male. Among all of the respondents, 15.8% of the elderly reported significant pain compare to 84.2% adults aged within 18 to 59 years old reported significant pain. More Malays reported significant pain (31.5%) compare to Chinese (18.2%). There are 50% unmarried patients reported significant pain compare to 23.5% of married respondents reported significant pain. The result also show that 25.5% working patients reported significant pain while 32.4% of non working patients reported significant pain. However, the differences in pain severity in relation to age, gender, ethnic, marital status and occupation were not significant (p>0.05). The study found that osteosarcoma patients and evidence of bone metastasized reported to have the highest prevalence of severe pain as compared to other cancer patients. This study found that more than two third cancer patients experienced mild pain of less than 4 scores (p>0.05). The three highest life activities that were being interfered by cancer pain were "life enjoyment" (mean=5.94, SD=2.46), "mood" (mean=4.12, SD=2.45) and "general activity" (mean=3.4, SD=2.99) The limitation of this study is its small sample size. Some cancer patients refused to participate due to pain from cancer and treatment. The study did not take into account the differentiation between disease related pain and treatment pain and the length of time patients were admitted to the hospital. Thus, it is recommended that future studies take into account the differentiation and length of hospitalization. The findings highlighted that sociodemographic data such as age, gender, ethnicity, marital status and occupation can influence cancer patient's perception and responses to pain in difference ways. Thus, the nurses' awareness of the overall pain severity experienced by cancer patients is important.